ASSESSMENT OF ECOLOGICAL STATE OF THE VELIKAYA RIVER DELTA BASED ON HYDROCHEMICAL INDICATORS AND STRUCTURE OF PHYTOPLANKTON (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The basis of the existence of freshwater ecosystems is phytoplankton, which produces most of the primary biological production, participates in repair processes and provides a wide range of ecosystem services. The short life cycle and high speed metabolism of microalgae make them ideal objects for ecological monitoring.The aim of the present study is to research the ecological state of the Velikaya river delta based on the species composition of phytoplankton community and some hydrochemical parameters.The sample collection for phytoplankton study and physicochemical measurements was carried out in summer 2016 at five stations representing different ecological locations of the Velikaya river delta. One hundred sixty five species taxa of microalgae belonging to 8 phylums were identified during the research: Bacillariophyta (37%), Chlorophyta (33.9%), Cyanophyta/Cyanobacteria (9.7%), Chrysophyta (6.1%), Euglenophyta (6.1%), Cryptophyta (3%), Dinophyta (3%), Xanthophyta (1.2%).The values of Shannon index indicate the average complexity of the microalgae communities structure. Values of Margalef index characterize the Velikaya river delta as an area of high species richness. Compared to the previous studies, a significant increase in the level of information diversity is observed, indicating an increase in the number of possible flows of substance and energy in the ecosystem. Dynamics of biogen substances in the water shows a slight increase of their concentrations.Ecological and geographical analysis proves that absolute dominance of cosmopolitan freshwater forms is typical for the algoflora of the Velikaya river delta. In relation to the pH-reaction inhabitants of neutral and slightly alkaline water dominate. Pantle–Buck saprobity index is applied for water quality assessment, which shows beta-mesosaprobic water quality in the ecosystem. Thus, the water of the Velikaya river delta could be referred to the category of moderately polluted water (class II of water quality). This is confirmed by the data of hydrochemical analysis.